Development of Ukrainian statehood and authorities of Carpathian Ukraine - S. Yu. Ivanov (Bulletin of Kharkiv National University of Internal Affairs)
The features and prerequisites for the declaration of Carpathian Ukraine’s independence are studied, and the process of establishing state authorities under the leadership of Augustine Voloshyn is traced. The focus is placed on the difficult foreign and internal political situation of the newly created Ukrainian state, and the reasons that prompted the government of Carpathian Ukraine to abandon the development of democratic values, on the basis of which the young state was to develop, are identified.